PENGARUH MODEL DISCOVERY TERHADAP HASIL BELAJAR TEMATIK MATERI GAYA DAN MANFAATNYA DI SEKOLAH DASAR - Della Septyani; Hery Kresnadi; Siti Halidjah (Universitas Tanjungpura, 2020)
Abstract This study aims to look at the effect of discovery models on learning outcomes of style materials and their benefits in thematic learning in fourth grade students of elemtary schools 56 west Pontianak. Thesis. Program for student learning material style and its benefits, such as the nature of the styles, various styles, grade IV public elememtary school west Pontianak. This study uses an pre-experimental design experimental type, with a one-group pretest-posttest experimental design. The population in this study is all grade IV students of 56 elementary schools in west Pontianak. The sample in this study was class IV A amounting to 39 as an experimental class. Data collection techniques, with data collection tools in the from of a test of 50 questions. Then the analysis is done using test. Based on the analysis results obtained tcount (61,56)>ttabel (39,80) then Ha is accepted. So it can be concluded there is an influence of learning outcomes between students using the N-Gain valu of 0,56 (medium criteria). This means that learning by applying the discovery model has a moderate effect on student learning outcomes in grade IV public elementary schools 56 Pontianak Barat. Keywords: Effect, Discovery Models, Learning Outcomes